Skin Manifestations of Insulin Resistance: From a Biochemical Stance to a Clinical Diagnosis and Management - González Saldivar, Gloria; Rodríguez Gutiérrez, René; Ocampo Candiani, Jorge; González González, José Gerardo; Gómez Flores, Minerva (2016)
Worldwide, more than 1.9 billion adults are overweight, and around 600 million people suffer from obesity. Similarly, *382 million individuals live with diabetes, and 40–50% of the global population is labeled at ‘‘high risk’’ (i.e., prediabetes). The impact of these two chronic conditions relies not only on the burden of illnesses per se (i.e., associated increased morbidity and mortality), but also on their increased cost, burden of treatment, and decreased health-related quality of life. For this review a comprehensive search in several databases including PubMed (MEDLINE), Ovid EMBASE, Web of Science, and Scopus was conducted. In both diabetes and obesity, genetic, epigenetic, and environmental factors overlap and are inclusive rather than exclusive.